2019
DOI: 10.1002/aenm.201803688
|View full text |Cite
|
Sign up to set email alerts
|

Intermixed Cation–Anion Aqueous Battery Based on an Extremely Fast and Long‐Cycling Di‐Block Bipyridinium–Naphthalene Diimide Oligomer

Abstract: By virtue of their high energy efficiency, facile scalability, intrinsic safety, not to mention low cost and environmental compatibility, aqueous batteries are being increasingly Aqueous batteries, particularly those integrating organic active materials functioning in a neutral pH environment, stand out as highly promising contenders in the stationary electrochemical storage domain, owing to their unparalleled safety, sustainability, and low-cost materials. Herein, a novel di-block oligomer, serving as the neg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…recently proposed a new intermixed charge‐storage mechanism by merging p‐ and n‐type organic moieties together into a short oligomer, which mitigates volume variations upon cycling of the material . Such an advanced p/n‐type organic scaffold simultaneously stored ClO 4 − and Na + with an improved capacity (up to 105 mAh g −1 per mass of material) and high cyclability (over 6 500 cycles with 82.8 % retention at 2.4 A g −1 ) …”
Section: Insoluble Organic Electrodes In Aqueous Electrolytes For Enementioning
confidence: 99%
See 1 more Smart Citation
“…recently proposed a new intermixed charge‐storage mechanism by merging p‐ and n‐type organic moieties together into a short oligomer, which mitigates volume variations upon cycling of the material . Such an advanced p/n‐type organic scaffold simultaneously stored ClO 4 − and Na + with an improved capacity (up to 105 mAh g −1 per mass of material) and high cyclability (over 6 500 cycles with 82.8 % retention at 2.4 A g −1 ) …”
Section: Insoluble Organic Electrodes In Aqueous Electrolytes For Enementioning
confidence: 99%
“…For example, organics containing carbonyl groups are employed to build next‐generation batteries with organic electrolytes, such as Li (or Na) metal–organic batteries . Recently, organics have been employed in aqueous electrolyte for the fabrication of aqueous Li‐ion (also, Na‐ion or K‐ion) batteries, showing high cyclability and high power . However, it was found that the discharge products of monovalent metal cations (for example, C‐O‐Li + ) were easily oxidized by the dissolved O 2 in the aqueous electrolyte, leading to the problem of self‐discharge .…”
Section: Introductionmentioning
confidence: 99%
“…For example, organics containing carbonyl groups are employed to build next‐generation batteries with organic electrolytes, such as Li (or Na) metal–organic batteries . Recently, organics have been employed in aqueous electrolyte for the fabrication of aqueous Li‐ion (also, Na‐ion or K‐ion) batteries, showing high cyclability and high power . However, it was found that the discharge products of monovalent metal cations (for example, C‐O‐Li + ) were easily oxidized by the dissolved O 2 in the aqueous electrolyte, leading to the problem of self‐discharge .…”
Section: Introductionmentioning
confidence: 99%
“…With electricity increasingly generated from renewable resources such as solar and wind power, energy storage devices have become more and more indispensable in balancing the electricity supply and demand . Aqueous lithium‐ion batteries (ALIBs), featuring safety and long cycle life, could become a viable option serving as energy storage devices .…”
Section: Introductionmentioning
confidence: 99%